EKSPLORASI JENIS TUMBUHAN BERPOTENSI ANTI INFLUENZA DI KECAMATAN SUMBER HARTA - Nadia Sah Putri; Ivoni Susanti; Ria Dwi Jayati (Nusantara Hasana Journal, 2023)
Influenza is a contagious respiratory disease caused by the influenza virus, a sudden respiratory illness (acute respiratory illness) characterized by fever, sore throat, cough, and body malaise (restlessness). The disease spreads rapidly among people of all ages and causes large outbreaks or rapid outbreaks of infectious diseases (epidemic). Generally, the treatment of influenza uses synthetic drugs, but long-term use will have an impact on damage to other organs in the body. Therefore, one way to minimize the side effects of synthetic drugs is to use plants with potential anti-influenza. One of the Sumber Harta Subdistricts which still has land potential and the presence of abundant plants is Sumber Harta Subdistrict. The method used in this research is roaming with observation, interview, and documentation techniques. Based on the results of the study it was found that the number of plants found in Sumber Harta District was 20 species from 13 families of Anti-Influenza medicinal plants. The parts of the medicinal plants used by the people of Sumber Harta District amounted to 7 parts consisting of tubers, rhizomes, roots, stems, leaves, fruit. , and flowers, as well as the method of processing plants by the people of Sumber Harta District totaling 7 boiled, blended, grated, pounded, eaten directly, brewed and squeezed.